Role of γδ T cells in controlling viral infections with a focus on influenza virus: implications for designing novel therapeutic approaches - Ailar Sabbaghi; Seyed Mohammad Miri; Mohsen Keshavarz; Mehran Mahooti; Arghavan Zebardast; Amir Ghaemi (Virology Journal, 2020)
Abstract Background Influenza virus infection is among the most detrimental threats to the health of humans and some animals, infecting millions of people annually all around the world and in many thousands of cases giving rise to pneumonia and death. All those health crises happen despite previous and recent developments in anti-influenza vaccination, suggesting the need for employing more sophisticated methods to control this malign infection. Main body The innate immunity modules are at the forefront of combating against influenza infection in the respiratory tract, among which, innate T cells, particularly gamma-delta (γδ) T cells, play a critical role in filling the gap needed for adaptive immune cells maturation, linking the innate and adaptive immunity together. Upon infection with influenza virus, production of cytokines and chemokines including CCL3, CCL4, and CCL5 from respiratory epithelium recruits γδ T cells at the site of infection in a CCR5 receptor-dependent fashion. Next, γδ T cells become activated in response to influenza virus infection and produce large amounts of proinflammatory cytokines, especially IL-17A. Regardless of γδ T cells’ roles in triggering the adaptive arm of the immune system, they also protect the respiratory epithelium by cytolytic and non-cytolytic antiviral mechanisms, as well as by enhancing neutrophils and natural killer cells recruitment to the infection site. Conclusion In this review, we explored varied strategies of γδ T cells in defense to influenza virus infection and how they can potentially provide balanced protective immune responses against infected cells. The results may provide a potential window for the incorporation of intact or engineered γδ T cells for developing novel antiviral approaches or for immunotherapeutic purposes.